Upaya Meningkatkan Kemampuan Kosa Kata Bahasa Arab Siswa Kelas Satu Menggunakan Media Big Book - Anis Sutarwati (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2021)
The importance of language in communicating both locally and internationally cannot be overstated. Arabic is one of the sorts of languages that is taught at Indonesian madrasas. Arabic, being a foreign language, requires exposure to attractive media, notably large book media. The purpose of this study is to describe efforts made at State Madrasah Ibtidaiyah 3 Pangandaran to improve the language skills of first-graders through Big Book. This study used Classroom action research (CAR). The Kemmis and McTaggart models were employed in the investigation. The study was split into two cycles. Each cycle consists of two meetings include planning, acting, observing, and reflecting. This study found that The Big Book media can improve students’ Arabic vocabulary in first-graders State Madrasah Ibtidaiyah 3 Pangandaran.